Use of water treatment sludge as partial cement replacement in concrete mixtures - Cunanan, Johanna Marie M.; Porto, Jillian Ruth H.
Water treatment sludge (WTS) production is continuously increasing due to higher demand for drinking water. Different methods on reusing WTS have been studied to alleviate its disposal problems. This study investigated the use of WTS as cement replacement by mass in concrete mixtures by utilizing sludge-cement replacement percentages of 0%, 5%, 10% and 20%. The workability of the mixture, acidity, compressive strength, and water absorption rate of concrete samples produced were determined. Using One-way ANOVA and Tukey Pairwise Comparison Test, results showed that increasing sludge concentration does not affect concrete acidity, while it decreases compressive strength and increases workability of the resulting mixture. Water absorption rate is not significantly affected except for the 20% sludge concentration. The study concluded that maximum amount of WTS for cement replacement is 10% without compromising compressive strength, acidity and durability of concrete, which can still be used for non-structural applications such as concrete for borders, sidewalk and filling applications.